Transformational Leadership, Trust, and Motivation Driving Employee Performance and Retention - Dasep Suryanto; Crisdina Wempi; Mayang Lalita Ratri (Goodwood, 2025)
Purpose: This study explores the impact of transformational leadership communication behavior on employee trust, motivation, performance, and retention at PT Ace Hardware Indonesia, Tbk. Research Methodology: A quantitative approach was employed, and questionnaires were distributed to 300 employees. The collected data were analyzed using Smart PLS 3 to examine the relationships among the variables and test the mediation effects. Structural equation Modeling (PLS-SEM). Data were collected using a structured questionnaire distributed to 210 employees of a national television broadcasting company. The analysis was conducted using SmartPLS 4.0. Results: The findings indicate that transformational leadership communication behavior significantly influences employees’ trust, motivation, performance, and retention. Additionally, employee trust and motivation significantly mediated the relationship between transformational leadership communication and both performance and retention. Conclusions: This study demonstrates the complex interplay among transformational leadership, trust, motivation, performance, and retention, highlighting the critical role of leadership communication in fostering positive employee relationships. Limitations: This study is limited to a single company context and a cross-sectional design, which may affect its generalizability. Future research should consider longitudinal approaches and multiple organizational settings in this context. Contributions: This study provides practical guidance for implementing effective transformational leadership practices to enhance trust, motivation, and retention. It also contributes to the theoretical development of transformational leadership and offers directions for future research on organizational behavior.